Efectos psicológicos de la exposición a pantallas en la infancia. - Pilco Hurtado, Paola Anais (2025)
ABSTRACT: The early use of screens as a means of entertainment has become relevant in recent years, since the excessive use of devices can cause adverse effects that hinder the proper development of infants. Therefore, this research aims to analyse the psychological effects of screen exposure on children through a systematic review of articles. This work is of a documentary, bibliographic and descriptive level, the analysis of 13652 articles was considered and finally we worked with a total of 20 quantitative articles that investigated the variables of psychological effects and exposure to screens in Spanish and English published in the time period from 2020 to 2024 on scientific data such as Web of Science, Scopus, Google Academic and Pub Med, using the Boolean operators "AND" and "OR". These articles were selected through the application of specific selection filters and methodological quality assessment using the Critical Review Form - Quantitative Studies (CRF-QS) matrix. The results showed that prolonged exposure to digital media can lead to cognitive (attention, memory, problem solving and language) and socioemotional (prosocial behavior, communication, peer problems, emotional lability and anxiety) alterations.